2000
DOI: 10.1177/073346480001900106
|View full text |Cite
|
Sign up to set email alerts
|

Older Nonmetropolitan Residents' Evaluations of Their Transportation Arrangements

Abstract: This article uses data from focus groups to examine how older nonmetropolitan residents of upstate New York construct their transportation arrangements during different stages of the life course. The article also analyzes the effectiveness of different modes of transportation in facilitating life-maintenance and higher order needs of older individuals. Almost universally, youngold (age 65 to 74) rural residents drive themselves to most of their activities; a small proportion also use public buses to fill some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 14 publications
(19 reference statements)
9
75
0
2
Order By: Relevance
“…As a result, they perform much of their travel during the midday and on weekends (Collia et al 2003). During these off-peak times, xed-route transit service tends to be less frequent than it is during weekday peak hours (Glasgow and Blakeley 2000;Hayden et al 2004;Nelson 2002;Taylor et al 2000).…”
Section: Travel Patterns and Destinationsmentioning
confidence: 99%
“…As a result, they perform much of their travel during the midday and on weekends (Collia et al 2003). During these off-peak times, xed-route transit service tends to be less frequent than it is during weekday peak hours (Glasgow and Blakeley 2000;Hayden et al 2004;Nelson 2002;Taylor et al 2000).…”
Section: Travel Patterns and Destinationsmentioning
confidence: 99%
“…The car meets the majority of transport needs of older people by fulfilling most of the conditions that Metz [6] describes as defining mobility (access to desired places; psychological benefits of travel; benefits of physical movement; maintaining social networks and maintaining potential travel). It also provides autonomy, flexibility and independence [18], it is available at any hour and allows desired destinations to be reached conveniently [19]. Moreover, it can compensate for health impairments, allowing older people to be independent when undertaking daily activities [20].…”
Section: Introductionmentioning
confidence: 99%
“…Stopping driving can be perceived as a loss of independence [19,29] and is strongly associated with symptoms of depression [30,31]. Furthermore, the car remains the preferred mode of transport once driving has been given up, since asking for a lift from family or friends is considered the first option for people who cannot drive [18,19,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…Participants from Hervey Bay provided perspectives on a regional bus service, and participants from Brisbane represented users of a metropolitan bus service. The two sites were selected to provide divergent perspectives, as transport disadvantage is known to differ between metropolitan and more rural contexts (Glasgow and Blakely 2000).…”
Section: Samplingmentioning
confidence: 99%
“…In Australia, for instance, the proportion of older people is expected to at least double in the first half of this century (Alsnih and Hensher 2003). Older people have a greater risk of difficulty catching buses and other forms of public transport, despite an increased reliance on public transport for community mobility (Glasgow and Blakely 2000;Dent et al 1999;Davey 2007). In a study involving 620 older Australians (age 75 and over), a third reported difficulty using public transport (Dent et al 1999).…”
Section: Introductionmentioning
confidence: 99%